The Influence of Problem Based Learning on Problem Solving Ability in Science Materials in Elementary Schools - Annisa Yola Shafarina; Ali Mustadi; Siwi Purwanti (Postgraduate, University of Mataram, 2024)
Problem solving abilities have a significant role in increasing students' cognitive capacity, however, there are still difficulties in developing these skills. This research aims to assess the influence of the Problem Based Learning Model on students' problem solving abilities. This research is a quasi-experimental quantitative type with a pretest-posttest control group design. Fourth semester students in classes C and D of the PGSD Study Program were taken as samples using the Purposive Sampling technique. Data was collected through a research instrument in the form of a problem solving ability test in the Elementary School Science Learning Materials course. The results of hypothesis analysis using the Mann-Whitney test show the Asymp value. Sig. (2-tailed) is 0.000, which is smaller than 0.005. Therefore, it can be concluded that Hypothesis is Accepted. This means that there are differences between the experimental class which uses the PBL model and the control class with conventional learning. Thus, it can be concluded that the PBL model has an influence on the problem solving abilities of PGSD students.